(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
The study aimed to evaluate the protective role of aqueous extract of fenugreek seeds against ibuprofen-induced hepatic and renal damage in 24 adult male rabbits. They were divided into: control group; ibuprofen group (40 mg/kg); fenugreek extract group (100 mg/kg); and a group treated with ibuprofen + fenugreek extract (40 and 100 mg/kg, respectively). Histological examinations showed liver damage in the ibuprofen group, including central vein congestion, mononuclear cell infiltration, Kupffer cell activation, and portal vein congestion. The renal tissue showed glomerular shrinkage, Bowman’s capsule dilation, peritubular hemorrhage, and leukocyte infiltration. Liver enzymes (ALP, AST, ALT) and urea, creatinine, and uric acid levels were elevated, indicating hepatic and renal damage, more pronounced in the ibuprofen group. The fenugreek-treated group maintained tissue structure and function, indicating a protective role against ibuprofen-induced damage.